Chili Consumption and Risk of Gastric Cancer: A Meta-Analysis. (2nd January 2021) - Du, Yanbin; Lv, Yuan; Zha, Wenting; Hong, Xiuqin; Luo, Qinghong
Abstract: Chili peppers are loved by people all over the world and have been indispensable vegetable for three meals a day. However, reports about the association between chili consumption and gastric cancer (GC) risk have been conflicting. So, we carried out this meta-analysis to evaluate the effect of chili consumption on the risk of GC. Medline, PubMed, Web of science, Embase, Cochrane Library databases were systematically searched until May 2019. Heterogeneity among studies was examined using Q and I 2 statistics. Combined odds ratio (OR) with their 95% confidence interval (CI) were calculated using a random- or fixed-effects model. All data were analyzed using STATA 15.1 software. 13 studies (3, 095 cases and 4, 761 controls) were included in the meta-analysis. A 1.96-fold increased risk of GC was shown for the moderate-high chili consumption (OR = 1.96, 95%CI =1.59−2.42). Dose-response analysis showed a significant nonlinear association of GC risk with capsaicin intake (pnon-linearity <0.05) and suggested a significant positive association between high chili consumption and GC risk (OR = 2.28, 95%CI = 1.76–2.96) but not moderate chili consumption (OR = 0.72, 95%CI = 0.36–1.41). Sensitivity analysis and publication bias test results indicated that no publication bias and the results were reliable (Egger's: P  = 0.288). Evidence from this meta-analysis suggested that a higher level of chili consumption may be associated with an increased incidence of GC. More studies are warranted to confirm the association between chili consumption and the risk of GC.